2010
DOI: 10.1161/circheartfailure.108.824888
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Diastolic Reserve in Patients With Heart Failure and Normal Ejection Fraction

Abstract: Background-The genesis of symptoms in patients with heart failure (HF) and normal ejection fraction (HFNEF) is unclear. Most investigations of HFNEF have focused on cardiac function at rest although most of these patients are breathless only on exercise. Stress-induced impairment in systolic or diastolic function could result in these symptoms. Method and Result-Forty-one patients with HFNEF and 29 controls underwent dobutamine stress echocardiography with color tissue Doppler imaging. Wall motion score index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 54 publications
4
42
0
2
Order By: Relevance
“…The current study enrolled subjects with an earlier stage of HFpEF, where filling pressures were closer to normal at rest and physical examination evidence of congestion was largely absent. Despite the absence of right-sided structural remodeling, RV systolic and diastolic function were significantly impaired in the HFpEF group, differences that became more evident in the setting of β-stimulation, similar to prior studies evaluating LV-systemic arterial reserve with adrenergic stimulation [9][10][11][12][13] or exercise stress. 36,37 In HFpEF subjects, tricuspid annular s′ increased with dobutamine in relation to afterload reduction from dobutamine rather than an increase in contractility, which would manifest by an upward shift in the s′ versus PA pressure relationship.…”
Section: Rv Dysfunction and Rv-pa Coupling In Hfpefsupporting
confidence: 76%
“…The current study enrolled subjects with an earlier stage of HFpEF, where filling pressures were closer to normal at rest and physical examination evidence of congestion was largely absent. Despite the absence of right-sided structural remodeling, RV systolic and diastolic function were significantly impaired in the HFpEF group, differences that became more evident in the setting of β-stimulation, similar to prior studies evaluating LV-systemic arterial reserve with adrenergic stimulation [9][10][11][12][13] or exercise stress. 36,37 In HFpEF subjects, tricuspid annular s′ increased with dobutamine in relation to afterload reduction from dobutamine rather than an increase in contractility, which would manifest by an upward shift in the s′ versus PA pressure relationship.…”
Section: Rv Dysfunction and Rv-pa Coupling In Hfpefsupporting
confidence: 76%
“…22) On the other hand, in the two studies performed in patients with heart failure with preserved ejection fraction (HFPEF), the E/e' ratio was significantly higher with exercise in the patient group when compared to the controls and this increase was correlated with exertional dyspnea. 20,23) In a stress echocardiography study conducted by Podolec, et al in patients with ischemic heart failure, an increase of the E/e' ratio with exercise was the most important determinant of reduced exercise capacity in this patient population. 24) Briefly, an exercise induced increase in the E/e' ratio seems to be a good predictor of reduced ventricular compliance and decreased exercise capacity.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, it was recently reported that patients with diastolic dysfunction may present impaired diastolic reserve under stressful conditions [27], and this possibly explains weaning intolerance. In line with the above, other authors suggested that weaning outcomes may improve with the application of strategies aiming to manage heart failure (i.e., diuretics, nitroglycerin) [17,28,29].…”
Section: Discussionmentioning
confidence: 99%